1988
DOI: 10.1002/ana.410230217
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in myotonic dystrophy

Abstract: Seventeen of 25 patients with myotonic dystrophy had moderate to severe hearing loss, usually sensorineural, that was identified by routine audiometric screening and was treatable in some patients. Further testing failed to reveal a single pathophysiological process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
1
9
0
3
Order By: Relevance
“…Comparing DM1 and DM2, an autosomal dominant locus for hearing impairment (DNFA4) has been found adjacent to the DM1 locus on chromosome 19; 21 interestingly, hearing impairment has been described as part of the DM2/PROMM Mapping of DFNA18 adjacent to DM2 D Bo Ènsch et al 168 phenotype in some patients, 15 again similar to findings in patients with classical DM1 where deafness has been described as the only presenting symptom in some patients. 16 It has been discussed that the extension of the CTG repeat in the DMPK gene might produce a complex and possibly variable phenotype through its action on the expression of neighbouring genes. 28,29 For ophthalmic symptoms, a feature present both in DM1 and DM2, involvement of several genes has already been shown 30 and SIX5, a gene immediately downstream of DMPK seems to be involved in pathogenesis of cataract in DM1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing DM1 and DM2, an autosomal dominant locus for hearing impairment (DNFA4) has been found adjacent to the DM1 locus on chromosome 19; 21 interestingly, hearing impairment has been described as part of the DM2/PROMM Mapping of DFNA18 adjacent to DM2 D Bo Ènsch et al 168 phenotype in some patients, 15 again similar to findings in patients with classical DM1 where deafness has been described as the only presenting symptom in some patients. 16 It has been discussed that the extension of the CTG repeat in the DMPK gene might produce a complex and possibly variable phenotype through its action on the expression of neighbouring genes. 28,29 For ophthalmic symptoms, a feature present both in DM1 and DM2, involvement of several genes has already been shown 30 and SIX5, a gene immediately downstream of DMPK seems to be involved in pathogenesis of cataract in DM1.…”
Section: Discussionmentioning
confidence: 99%
“…The DM2/PROMM locus was originally mapped to chromosome 3q22 12 neighbouring DFNA18, and a number of PROMM disease pedigrees have been mapped to the same locus and are considered allelic to DM2. 13,14 DM2 and PROMM are characterised by myotonia, proximal weakness and cataracts; in PROMM disease, hearing loss has been described as one clinical feature 15 and is thus similar to myotonic dystrophy (DM1) located on chromosome 19, in which hearing loss has been reported as the only presenting symptom in some pedigrees, 16 and where it has been suggested that CTG repeats within the DMPK gene may result in variable expression of different genes clustering within the region and thus produce a more complex phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was repeated three times and data are expressed as mean ± standard error of the mean. auditory system (Huygen et al, 1994;Wright et al, 1988). Recently our group also reported that cochlear impairment in DM1 is present, even in patients without evidence of hearing loss as determined by a standard audiometric analysis (Pisani et al, in press).…”
Section: Discussionmentioning
confidence: 87%
“…Among the symptoms of DM1, myotonia and insulin resistance are attributed to the disruption of the CLCN-1 and IR alternative splicing, respectively (Charlet et al, 2002;Savkur et al, 2001). Moderate to severe hearing loss, usually sensorineural, has also been reported in DM1 patients (Wright et al, 1988) and the risk of developing serious hearing impairment is much greater for adult patients in all age brackets when compared to the general population (Wright et al, 1988). However, the cause of hearing problems in DM1 patients is not well defined.…”
Section: The Myotonic Dystrophy Type 1 Spliceopathymentioning
confidence: 99%
“…PROMM/DM2 is characterized by myotonia, muscular dystrophy with proximal weakness, cardiac conduction defects, endocrine disorders and cataracts; hearing loss has been described as one clinical feature in PROMM disease (1), the majority of which seems to map to the DM2 locus on 3q. In myotonic dystrophy (DM1), localized on chromosome 19, hearing loss has even been reported as the only presenting symptom (2). We have previously mapped a locus for non‐syndromic autosomal‐dominant hearing loss, DFNA18, to a region on chromosome 3q22 (3), overlapping with the PROMM/DM2 locus.…”
Section: Polymerase Chain Reaction (Pcr) Primers For the Analysis Of mentioning
confidence: 99%